Pengaruh karakteristik keuangan dan inflasi terhadap return saham pada perusahaan perbankan yang terdaftar di bursa efek indonesia periode 2018-2022 - Zulfa, Salsabila; Pambudi, Januar Eky (Universitas Muhammadiyah Tangerang, 2024)
The aim of this research is to determine the influence of financial characteristics and inflation on stock returns in banking companies listed on the Indonesian Stock Exchange for the 2018-2022 period. This research uses quantitative methods with descriptive methods used to measure the impact of current ratio, return on assets, debt to equity ratio, and inflation on stock returns. The sample was 15 banks for 5 years, so the total observations processed were 75 amounts of data. Descriptive statistical analysis and data evaluation with Eviews for hypothesis testing. Data processing is assisted by Microsoft Excel and Eviews software. Based on the test, the contribution of Current Ratio (CR), Return on Assets (ROA), Debt to Equity Ratio (DER) and Inflation to Stock Returns is 38.6%. CR has a positive and significant influence on stock returns because the p-value is 0.0491 (< 0.05). ROA has a positive and significant influence on stock returns because the p-values are 0.0474 (< 0.05). DER has a positive and significant influence on stock returns because the p-value is 0.0372 (< 0.05). Inflation has a positive and significant influence on stock returns because the p-value is 0.0285 (< 0.05). The CR, ROA, DER and Inflation variables together (simultaneously) have an influence on stock returns because the p-values are 0.049186 (< 0.05).